2014
DOI: 10.1111/bph.12600
|View full text |Cite
|
Sign up to set email alerts
|

Novel GPCR paradigms at the μ‐opioid receptor

Abstract: Opioids, such as morphine, are the most clinically useful class of analgesic drugs for the treatment of acute and chronic pain. However, the use of opioids is greatly limited by the development of severe adverse side effects. Consequently, drug discovery efforts have been directed towards improving the therapeutic profile of opioid-based treatments. Opioid receptors are members of the family of GPCRs. As such, the recent GPCR paradigms of biased agonism and allosterism may provide novel avenues for more effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 62 publications
3
68
0
1
Order By: Relevance
“…This is similar to results obtained by Rivero et al (2012), where morphine was slightly biased toward b-arr2, although not significantly (Thompson et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is similar to results obtained by Rivero et al (2012), where morphine was slightly biased toward b-arr2, although not significantly (Thompson et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…35 S]GTPgS binding and b-arr2 recruitment in HEK293 cells for some endogenous ligands, and found that endo-1 and endo-2 were biased toward b-arr2 recruitment compared with leu-enkephalin (McPherson et al, 2010;Rivero et al, 2012;Thompson et al, 2015). In our study, only endo-1 was biased toward b-arr2 over […”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations